Cost‐effectiveness analysis of a low‐dose contraceptive levonorgestrel intrauterine system in Sweden. (17th June 2015) - Henry, Nathaniel; Hawes, Charlie; Lowin, Julia; Lekander, Ingrid; Filonenko, Anna; Kallner, Helena K.
Abstract Objective To evaluate the cost‐effectiveness of a novel intrauterine system, levonorgestrel intrauterine system 13.5 mg vs. oral contraception, in women at risk of unintended pregnancy. Design Cost‐effectiveness model using efficacy and discontinuation data from published articles. Setting Societal perspective including direct and indirect costs. Population Women at risk of unintended pregnancy using reversible contraception. Methods An economic analysis was conducted by modeling the different health states of women using contraception over a 3‐year period. Typical use efficacy rates from published articles were used to determine unintended pregnancy events. Discontinuation rates were used to account for method switching. Main outcome measures Cost‐effectiveness was evaluated in terms of the incremental cost per unintended pregnancy avoided. In addition, the incremental cost per quality‐adjusted life‐year was calculated. Results Levonorgestrel intrauterine system 13.5 mg generated costs savings of €311 000 in a cohort of 1000 women aged 15–44 years. In addition, there were fewer unintended pregnancies (55 vs. 294) compared with women using oral contraception. Conclusion Levonorgestrel intrauterine system 13.5 mg is a cost‐effective method when compared with oral contraception. A shift in contraceptive use from oral contraception to long‐acting reversible contraception methods could result in fewer unintended pregnancies, quality‐adjusted life‐year gains, as well as cost savings.